PROFIL KEMANDIRIAN BELAJAR PESERTA DIDIK KELAS VIII SMPN 1 PAKENJENG - Lina Yuliana Agustina; Teti Sobari; Wiwin Yuliani (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2019)
This study aims to determine the independence profile of the eighth grade students of SMPN 1 Pakenjeng. The sample involved was 54 people, with the transfer technique using the learning independence questionnaire. Based on descriptive quantitative data analysis techniques obtained research results as follows the learning independence profile of students in class VIII of SMP 1 Pakenjeng depending on the medium category. Learning independence by sex comparing the learning independence of female students is better than the learning independence of male students. The results of the study of learning independence in terms of aspects of learning independence found motivation and cognitive aspects more influence the learning independence of class VIII students compared to the aspects of motivation.Keywords:  Independence of learning, junior high school students